Native Valve Infective Endocarditis Caused by Histoplasma capsulatum in an Immunocompetent Host: The First Case in Asia and Literature Review in Asia and Australia. (21st June 2021) - Amnuay, Kamalas; Sirinawin, Chayatat; Theerasuwipakorn, Nonthikorn; Chattranukulchai, Pairoj; Suankratay, Chusana
Abstract : Background . Infective endocarditis caused by the dimorphic fungus Histoplasma capsulatum is extremely rare, occurring predominantly in individuals with prosthetic heart valves and HIV infection. To our knowledge, no case of H. capsulatum native valve endocarditis has been reported in Asia. Methodology . A descriptive study was carried out at King Chulalongkorn Memorial Hospital, Bangkok, Thailand, in 2020. Results . A previously healthy 34-year-old man developed fever, umbilicated skin lesions, oral ulcers, hoarseness of voice, severe weight loss, and progressive dyspnea over the course of one week. Facial umbilicated papules, nodular ulcers in his tongue and palate, a diastolic rumbling murmur at the mitral valve, diffuse fine crackles in both lungs, and engorged neck veins were detected during the examination. Skin scraping of the facial lesion revealed both extracellular and intracellular yeasts with buddings, 2–4  μ m in size on Wright's stain. Transthoracic echocardiography demonstrated a left ventricular ejection fraction of 54 percent, severe rheumatic mitral stenosis, and multiple oscillating masses in the anterior mitral valve leaflet ranging in dimension from 1.5 to 2.4 cm. The HIV antibody test was negative. H. capsulatum endocarditis was diagnosed, and liposomal amphotericin B was administered. Due to cardiogenic shock, emergency open-heart surgery was conducted one day after admission. However, he died of multiorgan failure four days after the operation. The skin and vegetation cultures finally grew H. capsulatum after 1 week of incubation. Conclusions . To date, there has been handful of cases of H. capsulatum native valve endocarditis in non-HIV-infected patients. We report herein the first case in Thailand. Umbilicated skin lesions, especially combined with oral mucosal lesions, are a clinical clue that leads to the correct diagnosis of the causative organism.